2016
DOI: 10.4314/jlt.v50i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Non-curricular postgraduate writing interventions at South African Universities

Abstract: Formalised postgraduate writing support centres are a relatively new phenomenon at the majority of South African universities and have not yet been researched intensively. This article, which forms part of a mandated study, presents the findings of research into the nature of postgraduate writing support at a number of South African universities. In 2014, an external review into the throughput rate of undergraduate and postgraduate students at a particular South African residential university was conducted, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…A discussion of main issues of the study is provided. Although a range of studies has identified ways authors can go about writing for specified audience (Feak & Swales, 2009, Bullock & Goggin, 2010, Swales & Feak, 2012and Vivian & Fourie, 2016), there appears to be a gap in the literature when it comes to addressing novice writers' needs when preparing or writing research-based articles for publication. This section surveys the literature regarding issues to be considered when writing various sections of a research-based article.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…A discussion of main issues of the study is provided. Although a range of studies has identified ways authors can go about writing for specified audience (Feak & Swales, 2009, Bullock & Goggin, 2010, Swales & Feak, 2012and Vivian & Fourie, 2016), there appears to be a gap in the literature when it comes to addressing novice writers' needs when preparing or writing research-based articles for publication. This section surveys the literature regarding issues to be considered when writing various sections of a research-based article.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The writer does this in a reasonable and respective tone in the presentation, to show an existence of a knowledge gap to be addressed in the article (Bullock and Goggin, 2010). Furthermore, the Introduction section needs to appropriately situate the work within the existing body of related studies in a way that helps the writer to create a space for the new work (Vivian & Fourie, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Rensburg, Mayers and Roets (2016) explain that "the role of the supervisor in providing a supportive, constructive and engaged supervision process is important to ensure that the future generation of students have the right educational and skills mix to fulfil the needs of the profession". Vivian and Fourie (2016) conducted a study in which they investigated the nature of support to students by supervisors at a selected number of universities in South Africa. The results of their study suggest that most universities in South Africa have formalised support for postgraduate students.…”
Section: Introduction and Background To The Studymentioning
confidence: 99%